PAXX, a paralog of XRCC4 and XLF, interacts with Ku to promote DNA double-strand break repair - Ochi, Takashi (Science, 2015)
XRCC4 and XLF are two structurally-related proteins that function in DNA double-strand break (DSB) repair. Here, we identify human PAXX (PAralog of XRCC4 and XLF; also called C9orf142) as a new XRCC4-superfamily member, and show that its crystal structure resembles that of XRCC4. PAXX interacts directly with the DSB-repair protein Ku and is recruited to DNA-damage sites in cells. Using RNA interference and CRISPR-Cas9 to generate PAXX(−/−) cells, we demonstrate that PAXX functions with XRCC4 and XLF to mediate DSB repair and cell survival in response to DSB-inducing agents. Finally, we reveal that PAXX promotes Ku-dependent DNA ligation in vitro, and assembly of core non-homologous end-joining (NHEJ) factors on damaged chromatin in cells. These findings identify PAXX as a new component of the NHEJ machinery.